2008
DOI: 10.1136/hrt.2007.121921
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of coronary artery disease and plaque morphology assessed by multi-slice computed tomography coronary angiography and calcium scoring in asymptomatic patients with type 2 diabetes

Abstract: MSCT angiography detected a high prevalence of CAD in asymptomatic patients with type 2 diabetes. A relatively high proportion of plaques were non-calcified (41%). Importantly, a calcium score <10 did not exclude CAD in these patients. MSCT might be a useful technique to identify CAD in asymptomatic patients with type 2 diabetes with incremental value over calcium scoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
90
1
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(104 citation statements)
references
References 29 publications
10
90
1
3
Order By: Relevance
“…In this study, approximately two-thirds of plaque volume was noncalcified, and the correlation between CAC and coronary CT angiography plaque index was only moderate (r = 0.47-0.57). The differences between CAC and PVI were greater in diabetic patients with low levels of CAC where CAC-based risk stratification is known to be poor and noncalcified plaque is more common (29). In addition to age and sex, CAC score was associated with hypertension, whereas plaque index was associated with BMI.…”
Section: Cardiac Imaging: Coronary Artery Plaque Volume and Obesity Imentioning
confidence: 76%
See 1 more Smart Citation
“…In this study, approximately two-thirds of plaque volume was noncalcified, and the correlation between CAC and coronary CT angiography plaque index was only moderate (r = 0.47-0.57). The differences between CAC and PVI were greater in diabetic patients with low levels of CAC where CAC-based risk stratification is known to be poor and noncalcified plaque is more common (29). In addition to age and sex, CAC score was associated with hypertension, whereas plaque index was associated with BMI.…”
Section: Cardiac Imaging: Coronary Artery Plaque Volume and Obesity Imentioning
confidence: 76%
“…Diabetic patients may have extensive noncalcified plaque not otherwise revealed with the CAC score (29), and lipid-containing plaque is greater in diabetic patients than in nondiabetic patients (30,31). CAC score is not a useful marker for assessing the reduction of plaque as a result of therapy, likely because CAC does not accurately reflect a change in modifiable noncalcified plaque (32).…”
Section: Cardiac Imaging: Coronary Artery Plaque Volume and Obesity Imentioning
confidence: 99%
“…In this study, we focused on two features of coronary artery plaque, namely, positive remodeling and low attenuation. Although a number of previous studies have described coronary CT angiography of diabetic patients, [14][15][16][17][18][19][20][21][22] our study is the first to focus on these particular features of plaque.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of significant stenosis of symptomatic patients and asymptomatic patients ranged from 33 to 42%, 15,19,21) and 15.2 to 29%, 16,20,22) respectively. A study containing both populations reported that the prevalence was 37%.…”
Section: Characteristics Of Coronary Ct Angiography Of Diabetic Patiementioning
confidence: 99%
“…Asymptomatic diabetic patients have also been evaluated using MSCT, 21 with the result of CAD in 80% of patients and significant stenosis in 26%. Although the prevalence of CAD was similar to our results (90%), significant stenoses were less prevalent (26% vs. 48%).…”
Section: Discussionmentioning
confidence: 99%